The relationship between gender or sex and mobility in middle and older aged community-dwelling adults with chronic conditions - Xu, Ying (My University, 2018)
The purpose of this thesis was to determine the relationships between gender or sex with mobility in middle aged and older community-dwelling adults with chronic conditions. Study one was a systematic review of published literature on whether gender or sex predict mobility in middle aged and older adults with chronic conditions in community-dwelling setting. Study two was a secondary analysis study (data from a randomized controlled trial where there were no statistically significant differences between rehabilitation intervention group and control group) to determine whether age and sex predict self-reported and performance-based mobility-related outcomes in community-dwelling middle and older aged adults with chronic conditions. This relationship was also examined in the context of sociodemographic and comorbidity variables. The information gained from these studies could be used to inform and guide future research and prevention intervention programs for people with risk of mobility limitation.
Keywords: gender; sex; age; mobility; chronic conditions; systematic review; secondary data-analysis